Handbook of pediatric otolaryngology a practical guide for evaluation and management of pediatric ear, nose, and throat disorders (World Scientific Pub. Co., 2012)
The Handbook of Pediatric Otolaryngology will provide the most up-to-date information on the clinical management of children with otolaryngologic disorders. It is ideal for medical students, house officers, and practicing physicians. Systems-based sections include information which is applicable in the clinic, operating room, and hospital settings. Chapters are written by experts in the fields of pediatric otolaryngology, anesthesiology, surgery, and audiology. It is an invaluable guide, in that it covers the basics of the specialty, while also including more advanced issues such as EXIT procedures, medico-legal controversies, and evidence-based medicine in pediatric otolaryngology. While it is a subspecialty text, it is written in a manner that is accessible to those at all levels of medical training